Fin whale (Balaenoptera physalus) identification and distribution around São Miguel island (Azores) and inferences on the movements towards other areas - Ernesto, Maria Ana Simões Reis (2021)
Understanding the movement patterns, and their possible drivers, of highly migratory marine species such as fin whale (Balaenoptera physalus), is vital for establishing appro-priate conservation measures. After been drastically reduced during the whaling period, fin whale populations are now recovering which led IUCN to recently update their status from “Endangered” to “Vulnerable”. Studying the population structure of the North At-lantic fin whales is particularly challenging due to their mobile nature and the lack of clear geographic barriers. The IWC (International Whaling Commission) suggests seven stock structure hypotheses however, there has been evidence of movements between these areas. The Azores archipelago is known to be a migration corridor for the North Atlantic populations, especially during springtime yet, many questions still exist regarding the ecology and habitat use in the archipelago. In this study, 11 years of opportunistic data from whale-watching platforms were used to create a photo-identification catalogue of fin whales around São Miguel. This catalogue was then compared with four other catalogues: one in the Azores and three from Iberian waters. The aim of this study was to assess potential migratory patterns and connections, understand the role of the Azorean archipelago and identify possible environmental driv-ers related to their presence. The composition of the photo-id catalogue and database en-abled the identification of 256 individuals and accounted for 32 re-sightings around São Miguel. The results presented indicate possible migratory connections within the archi-pelago and Galicia (North-West Spain), suggesting a variation of the commonly accepted migratory routes of baleen whales. Our findings also suggest that oceanographic features and events (e.g., phytoplankton spring bloom) influence the timing of fin whale migration and distribution in the archipelago. Additionally, this study serves as a baseline to further investigations, highlighting the important role of opportunist data in enhancing our knowledge of the biology and distribution of fin whales with the intention of supporting effective conservation measures and management programs to this emblematic species.